INTEGRATED POTENTIAL ASSESSMENT OF COMMUNITY-BASED ECOTOURISM IN DISTRICT A LUOI, THUA THIEN HUE PROVINCE - Dat, Ton That Huu (Vietnam Journal of Earth Sciences, 2014)
A Luoi is a mountainous dictrict with great potential for tourism development. The survey shows that there are a lot of good conditions for tourism development, especially community based ecotourism. However, the exploitation and using of this tourism resources in general and community based ecotourism in particular have yet to be effect and matching to available potential. Therefore, this paper conducted a qualitative and quantitative assessment of tourism potential in A Luoi, especially community based ecotourism to serve for planning and development of sustainble tourism. The results of qualitative assessment showed that tourism resources in Luoi district is rich and diverse, including natural beauty of pristine forests with diversity of flora and fauna, the natural waterfalls, the mineral springs, ... Moreover, tourism resources also include the ethnic community’s unique and rich cultures, such as traditional festival, traditional handicaft productions, … and many historical and cultural monuments in which peoples heroically againsted foreign invader’s war, such as military caves and tunnels, Fomer U.S special Forces Bases, … These tourism resources will help A Luoi district to develop different types of tourism, for example ecotourism, historical tourism, cultural tourism, and specially, community-based ecotourism. The paper has also synthetically assessed of 11 potential destinations for community-based ecotourism, the quantitative results showed that 3 destinations were huge potential and 8 destinations were potential for community based eco-tourism. References Agnes Kiss, 2004. Is community-based ecotourism a good use of biodiversity conservation funds?. Trends in Ecology and Evolution, Vol.19, No.5. Fennell D., 2003: Ecotourism. New York. Roultledge, 2nd edition. Hausler N. and Wolfang S., 2002. Training manual for Community-based Tourism. Tran Thi Mai Hoa, Huan Nguyen Cao Huan, Noma Haruo, 2010. Potential of Developing Community-based Ecotourism in Van Don District, Quang Ninh Province, VNU Journal of Science, Earth Sciences 26, pp. 128-140 Đỗ Thị Thanh Hoa, 2007. Báo cáo tổng kết đề tài: Nghiên cứu đề xuất tiêu chí khu du lịch sinh thái ở Việt Nam, Viện nghiên cứu Phát triển du lịch. Lindberg K., Megan E.W., Engeldrum D., 2002. Du lịch sinh thái: Hướng dẫn cho nhà lập kế hoạch và quản lý, tập 2, Hiệp hội Du lịch sinh thái. Phạm Trung Lương, 2002. Du lịch sinh thái: những vấn đề lý luận và thực tiễn tại Việt Nam. Nxb. Giáo Dục, Hà Nội. Manu, Isaac, Kuuder, Conrad-J.Wuleka, 2012. Community-Based Ecotourism and Livelihood Enhancement in Sirigu, Ghana. International Journal of Humanities and Social Science, Vol. 2, No. 18. Okazaki E., 2008. A Community-Based Tourism Model: Its Conception and Use, Journal of Sustainable Tourism, Vol. 16, No. 5. Trần Nguyễn Khánh Phong, 2012. Lễ hội Ariêu piing của người Pacô, Tạp chí nghiên cứu và phát triển, số 2, tập 91. Bùi Thị Hải Yến, 2010. Quy hoạch du lịch, Nhà xuất bản Giáo dục Việt Nam. UBND huyện A Lưới, 2012. Báo cáo tổng kết công tác Quản lý bảo vệ rừng - Phòng cháy chữa cháy rừng 2012, triển khai nhiệm vụ năm 2013. UBND huyện A Lưới, 2012. Sơ kết 03 năm (2010-2012) thực hiện Đề án Đào tạo nghề cho lao động nông thôn và dự kiến kế hoạch 2013-2015. UBND tỉnh Thừa Thiên Huế, 2005. Dư địa chí Thừa Thiên Huế, Nxb. Khoa học và Xã hội. UNEP, 2002. Ecotourism: Principles, Practices and Policies for Sustainability United Nations World Tourism Organization & United Nations Environmental Programme (UNWTO & UNEP), 2005: Making Tourism Mote Sustainable. A Guide for Policy Makers. WWF, 2001. Guidelines for Community-based Ecotourism.